Hypertension and Cardiovascular Remodelling in Rats Exposed to Continuous Light: Protection by ACE-Inhibition and Melatonin. (3rd July 2014) - Simko, Fedor; Pechanova, Olga; Repova Bednarova, Kristina; Krajcirovicova, Kristina; Celec, Peter; Kamodyova, Natalia; Zorad, Stefan; Kucharska, Jarmila; Gvozdjakova, Anna; Adamcova, Michaela; Paulis, Ludovit
Abstract : Exposure of rats to continuous light attenuates melatonin production and results in hypertension development. This study investigated whether hypertension induced by continuous light (24 hours/day) exposure induces heart and aorta remodelling and if these alterations are prevented by melatonin or angiotensin converting enzyme inhibitor captopril. Four groups of 3-month-old male Wistar rats (10 per group) were treated as follows for six weeks: untreated controls, exposed to continuous light, light-exposed, and treated with either captopril (100 mg/kg/day) or melatonin (10 mg/kg/day). Exposure to continuous light led to hypertension, left ventricular (LV) hypertrophy and fibrosis, and enhancement of the oxidative load in the LV and aorta. Increase in systolic blood pressure by continuous light exposure was prevented completely by captopril and partially by melatonin. Both captopril and melatonin reduced the wall thickness and cross-sectional area of the aorta and reduced the level of oxidative stress. However, only captopril reduced LV hypertrophy development and only melatonin reduced LV hydroxyproline concentration in insoluble and total collagen in rats exposed to continuous light. In conclusion, captopril prevented LV hypertrophy development in the continuous light-induced hypertension model, while only melatonin significantly reduced fibrosis. This antifibrotic action of melatonin may be protective in hypertensive heart disease.